The circular bioeconomy theories and tools for economists and sustainability scientists - Morone, Piergiuseppe (Cambridge University Press, 2023)
Interest in issues surrounding sustainable production-consumption systems and alternatives to fossil fuels is booming. The circular bioeconomy is currently mainstreamed in policy-making, industry and academia as an important part of the solution to the climate crisis and towards the creation of more sustainable economies. Based on the University-level teaching and research experience of the four authors in Italy, Finland, and France, this textbook fills an important gap in the literature by providing an in-depth and unique guide to the circular bioeconomy. The chapters critically discuss the potential contribution of a circular bioeconomy to fostering societal and organizational transformations towards sustainability globally. This timely book joins a suite of important new titles on sustainability, environmental and ecological economics.